Avebury, Yatesbury and the archaeology of communications - Andrew Reynolds (Papers from the Institute of Archaeology, 1995)
In this paper the application of archaeological techniques to the understanding of post-Roman routeways is explored with reference to the excavation and fieldwork currently being undertaken in and around Yatesbuty and Avebury, North Wiltshire, by the Compton Bassett Area Research Project (CBARP).
Keywords: communications; fieldwork